A Quality Improvement Approach to Standardization and Sustainability of the Hand-off Process. Issue 1 (6th April 2017) - Fryman, Craig; Hamo, Carine; Raghavan, Siddharth; Goolsarran, Nirvani
Abstract : There is mounting evidence that communication and hand-off failures are a root cause of two-thirds of sentinel events in hospitals. Several studies have shown that non-standardized hand-offs have yielded poor patient outcomes and adverse events. At Stony Brook University Hospital, there were numerous reported adverse events related to poor hand-off during the transfer of patient responsibility from one resident caregiver to the next. A resident-conducted root cause analysis identified lack of a standardized hand-off process and formal training on safe and efficient hand-off among caregivers as key contributing factors. This quality improvement project used the PDSA methodology to test the use of a standardized method, the IPASS mnemonic, and compare it to our conventional hand-off method in our internal medicine residency program. The main goals of this study were to test the feasibility and effectiveness of a standardized I- PASS hand-off and to create a robust sustainability model that includes 1) integration of I-PASS handoff in the Electronic Medical Record (EMR), 2) direct observation of the hand-off process by faculty and senior residents, and 3) surveillance and reporting of hand-off compliance scores. Compared to hand-off with a conventional method, the use of the I-PASS method resulted in significantly fewer reported adverse events (χ2=4.8, df=1, p=0.04). I-PASS was successfully integrated into our EMR system and residents were mandated to use this as the sole method of hand-off. An EMR audit conducted six months after implementation revealed poor compliance, which ultimately led to the creation of a sustainability model that improved overall compliance from 60% to 100%.